2023
DOI: 10.1108/ijshe-06-2022-0198
|View full text |Cite
|
Sign up to set email alerts
|

Perceived interest in learning sustainability competencies among higher education students

Abstract: Purpose This study aims to assess higher education students’ interest in learning sustainability competencies and their pro-ecological worldviews at a large research-intensive university in Finland to provide a background information for developing a sustainability science course. Design/methodology/approach In total, 797 students participated in the study. The data were collected through an online survey that measured students’ interest in learning sustainability competencies and their pro-ecological worldv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In addition, studies that come to the fore in the field literature focusing on sustainable awareness and environmental sensitivity within the scope of sustainable development (Hassan et al, 2010;Erkal et al, 2011;Kavaz & Öztoprak, 2019;Коstenko & Kuzmenko, 2021;Yılmaz et al, 2022;Hyytinen et al, 2023) are reflected in the results of this research.…”
Section: Discussion and Resultsmentioning
confidence: 75%
“…In addition, studies that come to the fore in the field literature focusing on sustainable awareness and environmental sensitivity within the scope of sustainable development (Hassan et al, 2010;Erkal et al, 2011;Kavaz & Öztoprak, 2019;Коstenko & Kuzmenko, 2021;Yılmaz et al, 2022;Hyytinen et al, 2023) are reflected in the results of this research.…”
Section: Discussion and Resultsmentioning
confidence: 75%
“…Students' SDK relies on other moderators such as environmental values (Qazi et al, 2021), student engagement (Cogut et al, 2019), institutional support (Lukman et al, 2020). Interest in learning sustainability competencies tended to differ among different programs, majors and fields which were found by (Hyytinen et al 2023) in their studies. This clearly testifies that LTI play little role in guiding the acquisition of SDK.…”
Section: Implications Conclusion and Future Researchmentioning
confidence: 99%
“…Recent studies have shown how students perceived critical thinking as one of the most interesting aspects of sustainability (Hyytinen et al, 2023). However, critical thinking, Critical and systemic thinking despite being a seminal objective of Higher Education (Puig et al, 2019), has been poorly developed in the field of PE.…”
Section: Competence In Critical Thinkingmentioning
confidence: 99%